Cage-like pores of a metal–organic framework for separations and encapsulation of Pd nanoparticles for efficient catalysis. (3rd February 2015) - Zhu, Yu; Wang, Yan-Mei; Liu, Pan; Wu, Yun-Long; Wei, Wei; Xia, Chang-Kun; Xie, Ji-Min
Abstract : A porous MOF can be applied for separation of organic compounds and drug delivery. It shows high catalytic reduction of 4-nitrophenol after embedding Pd NPs. Abstract : A porous metal–organic framework, {[Zn(BDC)1/2 (trz)]·DMAC} n (Zn-BDC), was synthesized hydrothermally with the decomposition of 2, 3-di(1, 2, 4-triazole)quinoxaline ligand (H2 BDC = 1, 4-benzenedicarboxylic acid; Htrz = 1, 2, 4-1 H -triazole). Structural analysis indicates the porosity of Zn-BDC with distorted oblong cages. Gas adsorption studies of N2 and Ar on activated Zn-BDC reveal the BET surface areas of 587.3 and 519.5 m 2 g −1, respectively. Considering the certain size of the cages, Zn-BDC can separate organic compounds with different sizes through a MOF-column chromatographic method and deliver 5-fluorouracil, which can act as an anticancer drug. Zn-BDC has also been employed as a support for Pd nanoparticles. The results of catalytic hydrogenation of 4-nitrophenol demonstrate that the catalytic activity of Pd@Zn-BDC is superior enough compared to most Pd catalysts reported.